Newly Licensed RN Retention: Hospital and Nurse Characteristics. (October 2017) - Blegen, Mary A.; Spector, Nancy; Lynn, Mary R.; Barnsteiner, Jane; Ulrich, Beth T.
Abstract : OBJECTIVES: The aims of this study were to examine the relationship between 1-year retention of newly licensed RNs (NLRNs) employed in hospitals and personal and hospital characteristics, and determine which characteristics had the most influence. METHODS: A secondary analysis of data collected in a study of transition to practice was used to describe the retention of 1464 NLRNs employed by 97 hospitals in 3 states. Hospitals varied in size, location (urban and rural), Magnet® designation, and university affiliation. The NLRNs also varied in education, age, race, gender, and experience. RESULTS: The overall retention rate at 1 year was 83%. Retention of NLRNs was higher in urban areas and in Magnet hospitals. The only personal characteristic that affected retention was age, with younger nurses more likely to stay. CONCLUSION: Hospital characteristics had a larger effect on NLRN retention than personal characteristics. Hospitals in rural areas have a particular challenge in retaining NLRNs.